TREN PENELITIAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS BUDAYA: TINJAUAN LITERATUR (2020-2025) - Fauziah, Anida; Widiarti, Nuni; Subali, Bambang; Ellianawati (Universitas Negeri Medan, 2026)
Abstract: The advancement of educational technology has not been fully accompanied by the use of diverse learning media. This study aims to analyze findings on the development of culture-based interactive learning media. A systematic review was conducted following the PRISMA 2020 guidelines, using articles from Crossref, Google Scholar, and Scopus. Of the 2,031 articles identified, 44 met the inclusion criteria for analysis. The findings show an increasing trend in culture-based media development up to 2022, particularly at the elementary level in IPAS, Mathematics, and Arts. Cultural integration enhances students’ motivation, learning outcomes, and cultural awareness. Future studies should expand implementation scales and integrate AR, VR, gamification, and artificial intelligence technologies. Keyword: Bibliometrics, Culture, Educational Technology, Interactive Media, Local Wisdom